The Relationship Between Infectious Diseases and the Nutritional Status of Children Under Five - Dwi Nurhastutik (Gema Bidan Indonesia, 2022)
Introduction: Undernutrition status (BB/U -3SD to <-2SD) is still common in developing countries such as Indonesia. Infectious diseases that often occur are ARI and diarrhea and affect the nutritional status of toddlers. Objective. The purpose of this literature review is to conduct a systematic review of several recent research results that examine the relationship between infectious diseases and toddlers nutritional status. Method. Search for articles using the Boolean strategic method by filtering articles using Flow Diagrams. Databases used are ProQuest, Pubmed, Science Direct, Research Gates, and Google Schoolar. International and national journals are indexed by SINTA and Scopus, so the articles used are reputable, with articles looking back 5 years. Results. 12 articles state that infectious diseases that occur in toddlers are ARI and diarrhea. 8 other articles mention other infectious diseases, namely tuberculosis, pneumonia, measles, and ear infections. 11 international articles discuss infectious diseases in toddlers, namely ARI and diarrhea are infectious diseases that often occur in toddlers in other developing countries such as East Africa, Bangladesh and Ethiopia. Infectious diseases and poor nutritional status in toddlers have a synergistic relationship. Conclusion. Infectious diseases that often occur in toddlers are ARI and diarrhea and are associated with toddlers nutritional status. Suggestion. Further research is needed on follow-up reviews to find out why ARI and diarrhea are diseases that often occur in toddlers in Indonesia and other developing countries. Keywords: Infectious disease; ARI; diarrhea; poor nutritional status.